2003
DOI: 10.1523/jneurosci.23-34-10815.2003
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Assembly of Transduction Apparatus in Chick Basilar Papilla

Abstract: Hair cells, the sensory receptors of auditory and vestibular systems, use a transducer apparatus that renders them remarkably sensitive to mechanical displacement as minute as 1 nm. To study the embryonic development of the transducer apparatus in hair cells of the chick auditory papilla, we examined hair cells that have been labeled with N-(3-triethylammoniumpropyl)-4-(4-(dibutylamino)styryl) pyridiniumdibromide, which has been shown to permeate the transducer channels. In addition, mechanotransduction curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 50 publications
8
53
0
Order By: Relevance
“…Data presented are similar to those described in avian auditory hair cells (Si et al, 2003) but for shift in the activation curve. In contrast to data presented here, the activation curve shifted from left to right in avian basilar papilla, indicating a large probability of opening that decreased during maturation.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Data presented are similar to those described in avian auditory hair cells (Si et al, 2003) but for shift in the activation curve. In contrast to data presented here, the activation curve shifted from left to right in avian basilar papilla, indicating a large probability of opening that decreased during maturation.…”
Section: Discussionsupporting
confidence: 73%
“…The all-or-none hypothesis suggests that the MET complex, including the adaptation components, assembles at the base of the stereocilia and migrates intact to the tops of the stereocilia. In contrast, data from chick basilar papilla (Si et al, 2003) revealed a maturation process in which the size of the MET current increased, adaptation got faster and more complete, and the current-displacement plot shifted rightward, meaning the resting open probability decreased during maturation. This pattern of development indicated that the MET complex assembly undergoes a period of refinement and consolidation.…”
Section: Introductionmentioning
confidence: 85%
“…Another similarity between ependymal cells and HCs is that ependymal cells express partially open large-conductance cation channels that are permeable to FM1-43 akin to mechano-sensitive channels in HCs. Ependymal cells show rapid (Ͻ60 s) FM1-43 uptake, which was inhibited by dihydrostreptomycin (26,27) (Fig. 4C1 and 2).…”
Section: Resultsmentioning
confidence: 93%
“…In addition, immunohistochemical techniques were used to examine the expression of cell-specific proteins. Assay for mechanosensory transduction used in our previous report (27) was adopted for ependymal cell.…”
Section: Methodsmentioning
confidence: 99%
“…Concurrently, hair cells begin to take up FM1-43 and exhibit mechanotransducer currents between E16 and E17 (Géléoc and Holt, 2003). Chicken and mice cochlear hair cells follow the same sequence (Si et al, 2003;Waguespack et al, 2007;Lelli et al, 2009).…”
Section: Developmental Acquisition Of Mechanosensitivity In Tether Cellsmentioning
confidence: 99%